Polymorphism in HTR3D shows different risks for acute chemotherapy-induced vomiting after anthracycline chemotherapy. (July 2010) - Hammer, Christian; Fasching, Peter A; Loehberg, Christian R; Rauh, Claudia; Ekici, Arif B; Jud, Sebastian M; Bani, Mayada R; Beckmann, Matthias W; Strick, Reiner; Niesler, Beate
Aims: Serotonin (5-hydroxytryptamine 3; 5-HT3 ) receptors are involved in chemotherapy-induced nausea and vomiting (CINV), and 5-HT3 antagonists are part of the 'gold standard' antiemetic treatment during chemotherapy. We investigated the correlation of common variants in 5-HT3 receptor subunit genes with the occurrence of CINV.Materials & methods: A total of 110 previously characterized chemotherapy-naive women with primary breast cancer treated with anthracycline-containing chemotherapy served as a study group for mutational analysis by direct sequencing. Eight common SNPs in the 5-HT3 receptor genes, HTR3A, HTR3B, HTR3D and HTR3E, were selected for association analysis.Results: A nonsynonymous variant in HTR3D, p.G36A (rs6443930), was found to be over-represented in nonresponders, assuming a log-additive inheritance model (p = 0.048). Cox proportional regression analysis resulted in a hazards ratio of 0.36 for homozygous carriers of the C allele to vomit within 24 h after first chemotherapy administration (p = 0.049).Conclusion: Our data supports the hypothesis that 5-HT3 receptors play an important role in the pathogenesis of CINV. Along with previously identified HTR3 polymorphisms, the HTR3D p.G36A variant could also contribute to facilitating individual risk predictions.